Molecular and physiological characterization of transgenic soybean (Glycine max) over-expressing oryzacystatin-I (OCI) in their root nodules - Makgopa, M.E. (Matome Eugene) (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.